Mengapa Publikasi Indeks Sinta Menurun Tahun 2025? - Wahyudin Darmalaksana (Gunung Djati Conference Series, 2026)
The surprising fact that the Sinta index publications declined in 2025 and the insignificant achievement in 2026 was significant. This study aimed to discuss effective strategies for increasing scientific publications. This qualitative study employed observation, and interviews to collect data, followed by phenomenological interpretation. The results indicate that academics in the 2023-2024 period were highly motivated in research and scientific publication, but their motivation weakened in the 2024-2025 period. The factors contributing to this decline, including the main factors, are discussed, and appropriate strategies are proposed. This study concludes that there is significant potential for academics, both lecturers and students, to continue productively increasing the number of scientific publications, not only in quantity but also in quality, as an effort to develop science, technology, and knowledge in Indonesia.